2003
DOI: 10.5507/bp.2003.020
|View full text |Cite
|
Sign up to set email alerts
|

Metal-chelating properties, electrochemical behavior, scavenging and cytoprotective activities of six natural phenolics

Abstract: Chelation, electrochemical, antioxidant and cytoprotective properties of six phenolics - cynarin and caffeic, chlorogenic, ferulic, protocatechuic and rosmarinic acids were studied on the following models: (i) chelation of transition metals, (ii) quenching of the diphenylpicrylhydrazyl radical (DPPH), (iii) determination of half-wave potential, (iv) erythrocytes or mitochondrial membranes damaged by tert-butyl hydroperoxide (tBH) and (v) a primary culture of rat hepatocytes intoxicated by Cu(II) and Fe(III) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 16 publications
0
56
2
2
Order By: Relevance
“…Despite known property of CA as an antioxidant [7,8], its administration in the present work had no significant effect on increased values of MDA in erythrocyte haemolysate of mice in group 3 as compared to lead-exposed animals in group 2. Despite the present findings, Psotova et al [32] reported that CA was able to decrease the augmented levels of lipid peroxidation and to eliminate intracellular GSH decline of hepatocytes intoxicated by Fe (III), Cu (II) and tertbutyl hydroperoxide. In addition, CA significantly reduced lipid peroxidation and restored the levels of antioxidant defense in the liver of rats intoxicated with nickel [8].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Despite known property of CA as an antioxidant [7,8], its administration in the present work had no significant effect on increased values of MDA in erythrocyte haemolysate of mice in group 3 as compared to lead-exposed animals in group 2. Despite the present findings, Psotova et al [32] reported that CA was able to decrease the augmented levels of lipid peroxidation and to eliminate intracellular GSH decline of hepatocytes intoxicated by Fe (III), Cu (II) and tertbutyl hydroperoxide. In addition, CA significantly reduced lipid peroxidation and restored the levels of antioxidant defense in the liver of rats intoxicated with nickel [8].…”
Section: Discussioncontrasting
confidence: 49%
“…The results of an in vitro study showed that some natural phenolics including caffeic, chlorogenic, ferulic, protocatechuic and rosmarinic acids behaved as antioxidants with chemoprotective effects in some low concentration ranges [32]. On the other hand, protocatechuic acid at concentrations above 2.5 mM showed in vitro pro-oxidation activity linked to the decrease in reduced glutathione and increase in cellular TBARS [33].…”
Section: Discussionmentioning
confidence: 99%
“…The intake of CA from foods mainly from tomatoes and potatoes was estimated to be about 0.2 mg/kg body weight per day (National Research Council 1996). Furthermore, CA exhibits multipharmacological effects such as antioxidant (Kono et al 1997), free radical scavenging (Gulcin 2006), and chelator of metal ions (Psotova et al 2003). A previous scientific report has revealed that CA inhibits oxidation of lowdensity lipoprotein in vitro and might therefore protect against CVD (Nardini et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…W badaniach in vitro wykazano, że chelatowanie jonów metali przez fenolokwasy chroni błonę komórkową przed uszkodzeniami indukowanymi przez jony metali przejściowych. Kwas kawowy może tworzyć kompleksy z jonami Cu 2+ , Fe 2+ oraz Fe 3+ [28]. Wiązanie jonów żelaza in vitro przez kwas kawowy badano, m.in.…”
Section: Właściwości Chelatujące Kwasu Kawowegounclassified